2006
DOI: 10.1111/j.1440-1681.2006.04513.x
|View full text |Cite
|
Sign up to set email alerts
|

TIME‐DEPENDENT TRANSITION FROM H2O2–EXTRACELLULAR SIGNAL‐REGULATED KINASE‐ TO O2–NITRIC OXIDE‐DEPENDENT MECHANISMS IN THE STIMULATORY EFFECT OF LEPTIN ON RENAL Na+/K+‐ATPase IN THE RAT

Abstract: 1. Recent studies suggest that leptin, a peptide hormone secreted by white adipose tissue, is involved in the pathogenesis of arterial hypertension, in part by regulating renal sodium handling. Previously, we have demonstrated that in normal rats leptin has a time-dependent effect on renal Na(+)/K(+)-ATPase that drives tubular sodium reabsorption. Short-term leptin infusion results in a transient decrease in Na(+)/K(+)-ATPase activity, whereas prolonged administration stimulates the enzyme. 2. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The results demonstrate that NADPH oxidase in HSCs regulates their activation process, so that the NADPH oxidase complex regulates liver fibrogenesis in response to Ang II, PDGF or apoptotic bodies. Since NADPH oxidase mediates the effects of several other agonists in extra-hepatic cells [89][90][91] (leptin, endothelin, homocystein), these potentially interesting agonists need to be assessed in HSC activation. Secondarily, two different NADPH oxidase forms, the phagocytic and the nonphagocytic form, are apparently both actively operating in liver fibrogenesis.…”
Section: Future Directionmentioning
confidence: 99%
“…The results demonstrate that NADPH oxidase in HSCs regulates their activation process, so that the NADPH oxidase complex regulates liver fibrogenesis in response to Ang II, PDGF or apoptotic bodies. Since NADPH oxidase mediates the effects of several other agonists in extra-hepatic cells [89][90][91] (leptin, endothelin, homocystein), these potentially interesting agonists need to be assessed in HSC activation. Secondarily, two different NADPH oxidase forms, the phagocytic and the nonphagocytic form, are apparently both actively operating in liver fibrogenesis.…”
Section: Future Directionmentioning
confidence: 99%
“…Recently, not only angiotensin II but also platelet‐derived growth factor (PDGF) and apoptotic bodies have been recognized as NADPH‐dependent agonists in HSCs 23. In addition, leptin‐induced ROS production in kidney and in smooth muscle cells is blocked by the NADPH oxidase inhibitor diphenylene‐iodonium (DPI) 24–26. In the liver, leptin is a fibrogenic agonist that may activate HSCs through H 2 O 2 production, but its relationship with NADPH oxidase has not been investigated 27…”
mentioning
confidence: 99%
“…To resolve why O 2 -• -NO mechanism predominates after 7-day systemic leptin administration [57] and H 2 O 2 -ERK dependent one after local 3-hour hormone infusion [63], we examined the effect of locally infused leptin in control animals as well as in rats made hyperleptinemic by preceding 7-day systemic leptin treatment [64]. Using combined biochemical and pharmacological approaches, we demonstrated that leptin infused locally to the renal artery stimulated cortical and medullary Na + ,K + -ATPase through the H 2 O 2 -ERK dependent mechanism in normal rats but through the O 2 -• -NO mechanism in previously hyperleptinemic rats, which suggests that the mechanism of antinatriuretic effect of leptin changes time-dependently when hormone is administered for prolonged time period.…”
Section: Time-dependency Of the Mechanism Through Which Leptin Stimulmentioning
confidence: 99%